Raye's group cross-country; arrests (sound roll 57) (1978)
Various meetings during a hike and contemplation on where to camp. Lots of singing and mentions of names within the group. There are lots of conversations about arrests and the police. The conversations of the police are based on how to avoid them. Helicopters, horns and nature sounds are heard throughout.